Performance bounds and suboptimal policies for multi-period investment - Boyd, Stephen P. 1958-; Mueller, Mark T.; Donoghue, Brendan; Wang, Yang (Now Publishers, 2014)
Examines dynamic trading of a portfolio of assets in discrete periods over a finite time horizon, with arbitrary time-varying distribution of asset returns. The goal is to maximize the total expected revenue from the portfolio, while respecting constraints on the portfolio such as a required terminal portfolio and leverage and risk limits
Description based on publisher supplied metadata and other sources